Smoking and alcohol specific alterations in miRNA expression in head and neck squamous cell carcinoma - Mohd Younis Bhat; Vishalakshi Nanjappa; Mariana Brait; David Sidrnasky; Aditi Chatterjee; Jayshree Advani (Discover Oncology)
Abstract Head and neck squamous cell carcinoma (HNSCC) is one of the most prevalent cancers worldwide with a high mortality in the advanced setting. Smoking and excessive alcohol consumption are major risk factors for the occurrence of HNSCC and contribute to a poor prognosis with continued use. In this study, we sought to identify the miRNAs that are dysregulated in response to smoking and alcohol consumption. miRNA-Seq datasets of HNSCC patients from The Cancer Genome Atlas (TCGA) were queried and included patients with (i) smoking exposure only (ii) alcohol consumption only (iii) exposure to both smoking and alcohol and (iv) no history of smoking or drinking alcohol. Our analysis led to the identification of 43 and 26 miRNAs that were differentially expressed in HNSCC patients with smoking only exposure and drinking only consumption, respectively. In addition, 37 miRNAs were altered in HNSCC patients who had a history of both smoking exposure and alcohol consumption compared to HNSCC patients with neither. The experimentally validated targets of these miRNAs were obtained from the miRTarbase database. Analysis of this dataset revealed that each exposure cohort exhibited distinct biological processes and pathways. The findings of this study indicate that smoking or alcohol consumption or both imparts different effects on miRNA expression which may lead to aberrant cell growth and eventually promote tumor progression and metastasis through distinct biologic effects.